Linking prenatal experience to the emerging musical mind - Ullal, Sangeeta; Vanden Bosch der Nederlanden, Christina M.; Tichko, Parker; Lahav, Amir; Hannon, Erin E. (Frontiers in Systems Neuroscience, 2013)
The musical brain is built over time through experience with a multitude of sounds in the auditory environment. However, learning the melodies, timbres, and rhythms unique to the music and language of one’s culture begins already within the mother’s womb during the third trimester of human development. We review evidence that the intrauterine auditory environment plays a key role in shaping later auditory development and musical preferences. We describe evidence that externally and internally generated sounds influence the developing fetus, and argue that such prenatal auditory experience may set the trajectory for the development of the musical mind.